Behaviour of walls constructed using Kelempayan (Neolamarckia cadamba) wood wool reinforced cement board - Zakiah Ahmad,; Lum, Wei Chen; Lee, Seng Hua; Wan Fatihah Wan Mohd Mahyiddin, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This research investigated the behaviour of walls produced from wood wool cement board (WWCB) which were reinforced with a lesser known commercial timber, Kelempayan, when subjected to compression load. Kelempayan timbers were shredded into wood wool and used as reinforcement agent in this study. WWCB having dimensions of 600 × 2400 × 50 mm and 600 × 2400 × 75 mm, respectively, were fabricated. Properties of the WWCB samples, namely swelling, bending and compression strength were tested. 75 mm WWCB has higher fracture toughness but lower strength compared to 50 mm WWCB. Four types of wall systems with different type of configuration were produced and the test results were compared focusing on their value of ultimate load and failure mode. Walls that constructed without application of link and plaster displayed the poorest performance. Plastered and linked wall had the highest ultimate load and comparable with other load bearing walls. The results suggested that walls constructed using WWCB reinforced with Kelempayan wood wool are suitable for load bearing as they exhibited comparable properties when compared to the other load bearing walls such as masonry and straw bale wall.